Outage probability due to crosstalk from multiple interfering cores in PAM4 inter-datacenter connections - Dias, R. (2021)
In this work, we propose to use four-level pulse amplitude modulation (PAM4) and multicore fibers (MCFs) to support very high capacity datacenter interconnect (DCI) links. The limitations imposed by inter-core crosstalk (ICXT) on the performance of 112 Gb/s up to 80 km-long optically amplified PAM4 inter-DCI links with intensity-modulation and direct-detection and full chromatic dispersion compensation in the optical domain are analyzed through numerical simulation for high and low skew-symbol rate product (SSRP). With only one interfering core, we show that those PAM4 inter-DCI links achieve an outage probability (OP) of 10−4 with a maximum ICXT level of −13.9 dB for high SSRP and require an ICXT level reduction of about 8.1 dB to achieve the same OP for low SSRP. Due to using full dispersion compensation, for an OP of 10−4, the maximum acceptable ICXT level shows only a 1.4 dB variation with the MCF length increase from 10 km to 80 km. When considering the ICXT induced by several interfering cores, the maximum ICXT level per interfering core for an OP of 10−4 decreases around 3 dB when doubling the number of interfering cores. This conclusion holds for high and low SSRP regimes. For two interfering cores, we show that a single interfering core with low SSRP is enough to induce a severe reduction of the maximum acceptable ICXT level.